Utilization of the Audacity Application as a Learning Media - Muhammad Taufiq; Tachioka Rexy; Asuncion Danyl; Phen Anoum (Lingeduca: Journal of Language and Education Studies, 2022)
The Audacity application is an application that is used through media in the form of a laptop without using data, and in the Audacity application, there are also many interesting menus that can be used by teachers or students in the use of learning media. And learning media is also a tool used by students in learning related to the material presented by the teacher. The purpose of this study, the author explain how to use the Audacity application as a learning medium at MAN 4 Tanah Datar. The method used by the author in this study is a qualitative method. The purpose of the qualitative method is a method in the form of an analysis of the author's thoughts regarding theories based on existing facts or in accordance with the elaboration studied by the authors from teachers related to Learning Media at MAN 4 Tanah Datar. The result is with rapid technological changes until now, students and teachers cannot be separated from the existence of learning media based on the Audacity application, the Audacity application is an application that is used for free, either by teachers or students and this application has many interesting features and used in learning